Evaluation of Learning in Cognitive, Affective and Psychomotor Aspects in Junior High School - Andriani, Ade; Syahfitri, Dian Vira; Manurung, Ardi Patchouli (Indonesian Journal of Education and Mathematical Science, 2025)
Evaluation of learning in Junior High School is very important in measuring student achievement in three main aspects: cognitive, affective, and psychomotor. The cognitive aspect focuses on the ability to think, understand, and apply knowledge, while the affective aspect is related to attitudes and values and the social emotional development of students. The psychomotor aspect assesses students' practical skills and abilities. This study uses a qualitative approach, with data collection through observation and interviews, and data analysis according to the Milles and Huberman method. The results of the study indicate that evaluation not only functions as a measuring tool, but also as feedback to improve the quality of learning. Therefore, an evaluation strategy is needed that includes various methods that can appreciate the uniqueness of each student and apply an inclusive and holistic approach. The conclusion of this study emphasizes that comprehensive evaluation will support children's development in a holistic and quality manner.